Self-stereotyping as "Evangelical Republican": An Empirical Test - Patrikios, Stratos (Politics and religion, 2013)
The prominence of evangelical Christians in the electoral base of the Republican Party is a noted feature of recent American elections. This prominence is linked to a key stereotype that saturates public discourse: "born-again/evangelical Republicanism." The stereotype fuses religious and partisan social group membership to create a composite social label. Using a social categorization approach, which challenges the assumptions and methods of existing research, the present analysis asks whether voters embrace this stereotype in their definitions of self. The article employs confirmatory factor analysis of religious and partisan identity constructs from a national internet survey, the 2008 Cooperative Congressional Election Study, and finds evidence of the presence of this religious-partisan stereotype in individual self-views, and of the backlash that it has produced, particularly among citizens that are exposed to public discourse on American elections.